2008
DOI: 10.2320/matertrans.mc2007109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rare-Earth Elements Y and Dy on the Deformation Behavior of Mg Alloy Single Crystals

Abstract: Effect of rare-earth elements (Y and Dy) on the mechanical properties of Mg solid solution single crystal is investigated. Comparing with the effect of other elements reported by previous studies, the solid solution strengthening by Y and Dy are much higher than that of other additives such as Zn for basal slip operation, while the isotropic strain by Zn atoms is higher than those of Y and Dy. Strain-rate changing tests were conducted for a further understanding of the dislocation motion and it revealed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 24 publications
0
47
0
2
Order By: Relevance
“…However, recent experimental studies [4,5,15,16] have demonstrated that Y and Gd exhibit anomalously higher solid solution hardening efficiency than those of Al and Zn in terms of the misfit parameters, which cannot be understood using the elastic interaction model. Such anomalous solid solution hardening of other RE elements, such as Ce [17] and Dy [18], was also reported. A few experimental and theoretical studies have been carried out to explore the solid solution hardening of RE in Mg.…”
mentioning
confidence: 63%
“…However, recent experimental studies [4,5,15,16] have demonstrated that Y and Gd exhibit anomalously higher solid solution hardening efficiency than those of Al and Zn in terms of the misfit parameters, which cannot be understood using the elastic interaction model. Such anomalous solid solution hardening of other RE elements, such as Ce [17] and Dy [18], was also reported. A few experimental and theoretical studies have been carried out to explore the solid solution hardening of RE in Mg.…”
mentioning
confidence: 63%
“…From the calculated theoretical elastic constants of the pure magnesium in Figure 2, it can be seen that the average differences between calculated and experimental data are less than 5%, which guarantee the accuracy of our calculations. As summarized in Figure 2(a) and (e), the addition of REEs results in an increase of c 11 and c 44 from La to Sm, followed by a decrease trend from Gd to Tm with abnormal low value at Eu and Yb, while c 12 , c 13 and c 33 in Figure 2 In order to examine the effect of doping concentration of rare earth elements, we substituted two RE atoms for Mg atoms in the supercell and obtained the Mg 52 RE 2 alloys. Thus, the concentration of rare earth elements increased to 1/27.…”
Section: Mechanical Propertiesmentioning
confidence: 91%
“…It is interesting that though the atomic size factor of Gd and Y is smaller than that of Al and Zn, they improve the mechanical properties more effectively than Al and Zn, according to Akhtar et al [9] and Gao et al [10]. Analogous phenomenon exists in Mg-Dy and Mg-Y alloys [11]. Gao et al [10] give an explanation of the anomalous hardening of Mg-Y and Mg-Gd alloy from the view of the increase of chemical bonding strength.…”
mentioning
confidence: 97%
“…It has been reported that addition of rare earth elements such as yttrium may improve mechanical properties over conventional Mg-Al-Zn alloys by minimizing intensity of the basal texture [5][6][7][8][9]. However, the deformation behavior of Mg alloys containing yttrium is not sufficiently understood at strain rates exceeding 1×10 3 s -1 .…”
Section: Extended Abstractmentioning
confidence: 98%
“…It has also been reported that a Mg-Al-Mn alloy had pronounced mechanical anisotropy at high strain rates of around 1.0×10 3 s -1 [4]. Therefore, the mechanical properties of Mg alloys should be evaluated accurately for applications involving possible dynamic loading.It has been reported that addition of rare earth elements such as yttrium may improve mechanical properties over conventional Mg-Al-Zn alloys by minimizing intensity of the basal texture [5][6][7][8][9]. However, the deformation behavior of Mg alloys containing yttrium is not sufficiently understood at strain rates exceeding 1×10 3 s -1 .…”
mentioning
confidence: 98%